Kerangka HAM Bagi Kebijakan Pengendalian Tembakau - Mulyana, Asep (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2014)
Production and consumption of cigarettes in Indonesia is very high have an alarming number of parties will be disruption of the right to health and public health. Some have urged the government to take steps to tobacco control. Steps to accede to the Framework Convention on Tobacco Control (FCTC) becomes an important effort exerted pro-tobacco control group. But the discourse of tobacco control for this still dwell on health issues as such. Not many people who put human rights as an effective instrument in the issue of tobacco control. In fact, besides the presence of a large wedge issue between tobacco control discourse and the discourse of human rights, the human rights approach also provides a reporting mechanism to ensure the operation of norms in international human rights treaties. Committee of the International Covenant on Economic, Social, and Cultural Rights (ICESCR) has issued recommendations to the Indonesian government to ratify the FCTC. Government of Indonesia, which became a state party to the ICESCR, should comply to that recommendation. Steps to accede to the treaty was not done in the era of old government (2009— 2014). Now the hope to ratify the treaty was based on the new government's commitment (2014— 2019) which campaigned for the protection of the rights of vulnerable groups, especially children. Accession FCTC is a form of government commitment on tobacco control in order to protect public health and the right to healt.